Analisis Efektivitas Kerja dari Peran Kepemimpinan Transformasional, Pemberdayaan Pegawai, dan Kualitas Komunikasi (Studi pada Pegawai LAPAS Kelas IIB Bireuen) - Martunis M. Harun; M. Yusuf; Sri Yanna (Singkite Journal, 2025)
Efforts to work effectively and efficiently strongly support the goals of the agency/organization, this is related to several factors such as leadership support, the existence of harmonious employee empowerment, and open communication space between personnel in a harmonious manner. This study examines this problem, with a quantitative approach with an associative type. Kzarena suspected that there is a causal relationship between them which has a direct and indirect impact on increasing employee work effectiveness. The study was conducted at the Class IIB Prison in Bireuen Regency. Based on data analysis with a path analysis model, it was obtained that (1) there is evidence between the variables of transformational leadership, employee empowerment, and communication quality that there is a causal relationship with an average very close. (2) Efforts to increase work effectiveness are directly and indirectly influenced by transformational leadership through employee empowerment, and communication quality by 55.09%. 3) Work effectiveness is directly and indirectly influenced by employee empowerment through transformational leadership and communication quality by 36.67%. (4) Work effectiveness is directly and indirectly influenced by communication quality through transformational leadership and employee empowerment by 40.52%. (5) Simultaneously, transformational leadership, employee empowerment, and communication quality impact employee work effectiveness by 81,7%.